A new species of Giovanella Bonatto (Diptera, Calliphoridae, Mesembrinellinae) from Colombia (2013)
ABSTRACT. A new species of Giovanella Bonatto (Diptera, Calliphoridae, Mesembrinellinae) from Colombia. The Mesembrinellinae are exclusively Neotropical, with 33 nominal species distributed in nine genera. Only the genera Mesembrinella, Eumesembrinella, Huascaromusca and Laneella had until now been recorded in Colombia. In this work we present a new species of Giovanella Bonatto, 2005, genus with only one species, G. bolivar Bonatto, differing from the new species G. carvalhoi sp. nov., in the characters: legs entirely dark chestnut; thorax with dorsocentrals setae 1:2; abdomen with T5 with discal bristles poorly differentiated; T6 symmetric and paraphallus not extended and with denticules. Giovanella carvalhoi sp. nov. is from Cordillera Oriental, from the Departments of Caquetá (Amazonian foothills) and Santander, Colombia, collected between 2200–2400 m., and associated with decomposing organic matter. A key for the identification of males and females of the two species of Giovanella, illustrations of the genitalia and photographs of male and female of new species are also presented.